2016
DOI: 10.1164/rccm.201508-1523oc
|View full text |Cite
|
Sign up to set email alerts
|

Central Sleep-disordered Breathing Predicts Incident Atrial Fibrillation in Older Men

Abstract: Rationale: Although research supports a sleep-disordered breathing and atrial fibrillation association, prospective data examining sleepdisordered breathing predicting incident atrial fibrillation are lacking.Objectives: To investigate sleep-disordered breathing indices as predictors of incident atrial fibrillation.Methods: A cohort (n = 843) of ambulatory older men without prevalent atrial fibrillation was assessed for baseline sleep indices: apnea-hypopnea index, central sleep apnea (central apnea index, >5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 52 publications
4
46
0
1
Order By: Relevance
“…Thus, our findings extend the previous work, in which CSA was more strongly associated with AF than OSA, but which were limited by cross‐sectional designs, which precluded assessment of the directional relationship between CSA and AF. More recently, a prospective analysis found that CSA and CSR predicted the risk of AF in a community‐based sample of older men . Our study extends these results by showing similar findings in both men and women across a wider age range, and further shows the persistence of findings even after adjusting for ECG‐based indices of left ventricular hypertrophy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, our findings extend the previous work, in which CSA was more strongly associated with AF than OSA, but which were limited by cross‐sectional designs, which precluded assessment of the directional relationship between CSA and AF. More recently, a prospective analysis found that CSA and CSR predicted the risk of AF in a community‐based sample of older men . Our study extends these results by showing similar findings in both men and women across a wider age range, and further shows the persistence of findings even after adjusting for ECG‐based indices of left ventricular hypertrophy.…”
Section: Discussionsupporting
confidence: 85%
“…Notably, approximately one quarter of those with CSA and 30% with CSA‐CSR developed AF, suggesting that the presence of CSA or CSR may be used to target individual patients for AF risk reduction. This is similar to estimates of AF and CSA from other cohorts . Further study is needed to understand the specific mechanisms underlying the association of central apnea and AF, and to evaluate the efficacy of treatment of CSA on the development, treatment, and prognosis of AF.…”
Section: Discussionsupporting
confidence: 73%
“…These disorders are subcategorized into obstructive sleep apnoea (OSA) disorders, central sleep apnea disorders, sleep-related hypoventilation disorders and sleep-related hypoxemia disorders [9]. It is well documented that SBDs are a risk factor for cognitive impairment [19], type 2 diabetes [20], early renal damage [21], heart failure [22], atrial fibrillation [23], coronary disease [24], as well as ischemic stroke [25]. The most common treatments for SBDs are continuous positive airway pressure (CPAP), surgery, oral appliances, postural therapy and weight loss.…”
Section: Effect Of Melatonin On Reducing the Complications Caused By mentioning
confidence: 99%
“…This sleep disorder rarely improves without treatment, and it may contribute to the progression of underlying cardiovascular disease and associated co-morbidities. 12 Although not proven, it can be hypothesized that reducing hypoxia and nocturnal arousals with phrenic nerve stimulation may decrease the associated risks of myocardial or cerebral ischemia, sympathetic activation, oxidative stress, inflammation, and endothelial dysfunction, which may also attenuate the progression of diseases such as heart failure. However, as previously described, 9 other therapies with mechanisms of action that differ substantially from phrenic nerve stimulation reduced AHI but have not improved survival or the composite end point of cardiovascular morbidity or mortality in patients with CSA.…”
Section: Discussionmentioning
confidence: 99%